2019
DOI: 10.1111/pedi.12956
|View full text |Cite
|
Sign up to set email alerts
|

“I'm essentially his pancreas”: Parent perceptions of diabetes burden and opportunities to reduce burden in the care of children <8 years old with type 1 diabetes

Abstract: Background: Across all age groups, management of type 1 diabetes (T1D) places substantial responsibility and emotional burden upon families. This study explored parent perceptions of the burdens of caring for very young children with T1D.Methods: Semi-structured qualitative interviews were conducted with parents (85% mothers) of 79 children with T1D, aged 1 to <8 years old, from four diverse pediatric diabetes clinical centers. Interviews were transcribed, coded, and analyzed using hybrid thematic analysis to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 22 publications
6
92
0
Order By: Relevance
“…The difficulty in finding someone reliable and used to the demands of diabetes is also challenging. This makes the role of caregiver a full-time job 2 . Despite these issues, concerns tend to be child-centered and the psychological demands of family members involved in childcare are often neglected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty in finding someone reliable and used to the demands of diabetes is also challenging. This makes the role of caregiver a full-time job 2 . Despite these issues, concerns tend to be child-centered and the psychological demands of family members involved in childcare are often neglected.…”
mentioning
confidence: 99%
“…Despite everything mentioned above, the psychological repercussion of the current scenario in guardians of children and adolescents with diabetes remains hypothetical. Several studies have shown that the deleterious effects of the caregiver's psychological distress apply to both caregivers and children, resulting in worse glycemic control and increasing the incidence of depression during adolescence 2,[5][6][7][8][9][10] . The care for caregivers' mental wellbeing, however, has received little priority when assessing the impact of stressful situations, such as the current pandemic of COVID-19 and the social distancing it requires 11 .…”
mentioning
confidence: 99%
“…Commissariat et al (2020) 19 Sullivan-Bolyai et al (2003) 5 Pimentel et al (2017) 3 Haslund-Thomsen et al (2020) 20 Povlsen et al (2009) 21 Martins et al (2014) 22 Kratzer (2012) 23 Seppänen et al (1999) 24 Lawton et al (2015) 25 Wennick et al (2007) 26 Wennick et al (2006) 27 Barone et al (2019) 28 Lowes et al (2014) 29 Sand et al (2017) 30 Nurmi et al (2012) 31 Symons et al (2015) 4 Pierce et al (2017) 1 Smaldone et al (2011) 32 Rifshana et al (2017) 33 Sullivan-Bolyai et al (2006) 34 Lowes et al (2005) 35 Spencer et al (2012) 36 Hatton et al (1995) 37 Khandan et al (2018) 38 Lowes et al (2004) 39 Marshall et al (2009) 40 Sparud-Lundin et al (2013) 41 Smith et al (2010) 42 Wennick et al (2009) 43 'Y' total for each question Albolhassani et al (2013) 18 Anderson et al (2018) 2 Commissariat et al (2020) 19 Sullivan-Bolyai et al (2003) 5 Pimentel et al (2017)…”
Section: Change Of Life Routine After Diagnosismentioning
confidence: 99%
“…Physical discomfort, body image concerns, the need to be connected to the device at all times, frequent alarms that disrupt daily life, and the expense of the technology are all frequently cited patient concerns regarding CGM use (44,(104)(105)(106)(107). Parents of young children with T1D indicate that they would like to receive targeted formal education to improve their knowledge of these technologies, thereby reducing the burden of diabetes management (108). Adolescents with more depressive symptoms and lower overall and diabetes-specific quality of life are less likely to use CGMs suggesting that recognition of these factors and appropriate intervention may improve device uptake in this population (109).…”
Section: Cgm Use and Patient Related Outcomesmentioning
confidence: 99%